2024
DOI: 10.21608/ejvs.2023.225910.1551
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Bacteriological Quality of Some Fish Products

Nady Elbarbary,
Doaa S. Abd El-aziz,
Mohamed A. Maky Maky
et al.

Abstract: F ISH products are considered a nutritionally significant component of the human diet because they contain macronutrients (proteins, fats, and ash) and micronutrients (vitamins and minerals). Accordingly, 200 different commercial fish product samples (25 each of canned solid tuna, canned chunks tuna, canned crumbled tuna, canned anchovy, canned mackerel, canned sardine, herring, and tilapia fillets) of different brands were collected from various local and high supermarkets in Aswan City during 2020-2021. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…On the other hand, A. hydrophila virulence-associated genes ( aerA and Act ) were found in 60% and 40% of the inspected A. hydrophila isolates ( Figure 3 ). These results matched Emeish et al [ 58 ] and Elbarbary et al [ 59 ], who recorded 64.3% and 60% of the inspected A. hydrophila isolates. The results were lower than those of Ahangarzadeh et al [ 60 ], who detected aerA and act genes in 51.61% and 74.19%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…On the other hand, A. hydrophila virulence-associated genes ( aerA and Act ) were found in 60% and 40% of the inspected A. hydrophila isolates ( Figure 3 ). These results matched Emeish et al [ 58 ] and Elbarbary et al [ 59 ], who recorded 64.3% and 60% of the inspected A. hydrophila isolates. The results were lower than those of Ahangarzadeh et al [ 60 ], who detected aerA and act genes in 51.61% and 74.19%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study revealed lower incidence rates of rpoB and lasB genes in P. aeruginosa isolates compared to the analysis shown by Benie et al [ 64 ], who detected rpoB and lasB I with incidences of 91.1% and 89.2%, respectively. Meanwhile, the current results were higher than those reported by Elbarbary et al [ 59 ] and Shahrokhi et al [ 70 ], who confirmed that the lasB gene (50%) had been the primary detected virulence gene in inspected P. aeruginosa isolates. These results indicate that some virulence factors assist bacterial establishment and colonisation on the surface of the host, while others expedite the invasion of numerous tissues.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations